MAKNA SIMBOL BENTUK DAN SENI HIAS PADA RUMAH BUGIS SULAWESI SELATAN - Pangeran Paita Yunus (LP2M ISBI Bandung, 2012)
The cosmologic view of the Buginese tribe assumes that this macrocosmos (the universe) is arranged into three levels: Boting langi’ (the upper world), Ale kawa (the middle world), Uri’ Li’yu’ (the Under world). As the centre from the three parts of this universe is Boting Langi (the highest sky), the place of Dewata SeuwaE (God) to lie down. This view is represented in the King’s Palace/traditional house building seen as the microcosmos. So, the King’s palace of the Buginese is devided also into three levels (stacks), those are: Rekkeang (top floor) viewed as the head of the human being, Alle bola (the body of the house) viewed as the body, and Awa bola (space underneath of the house) viewed as the leg of the human being. The three parts are centered at Posi’ bola or the house navel. This research tries to answer the problems: 1) whether the meaning form of the King’s Palace of the Buginese based on cosmology, and 2) how the symbol meaning of decorative art at the King’s Palace of the Buginese is. To identify and comprehend the meaning of decorative art on the King’s Palace of the Buginese, it is done through hermeneutic theory by Gadamer and the symbol meaning theory by Victor Turner. This research gives description that the happening of structural change and the style of decorated art at the kings’ palace of the Buginese of South Sulawesi, beside having much influence from the art of Dong-son and Chou Tua style, the decorated art at the Buginese tribe also got influence from Hinduism and Islam. In addition, the change of the art style is decided also by the one who has power in the society, either in the politic side or in the religion or culture. In this case, the existence of art style variation is caused by the existence of the levelling and groupping of the society.Keyword: Decorated art, Buginese tribe.